An empirical investigation of the effect of customer participation on ATM’S service performance. - Shivany, S. (University of Jaffna, 2011)
The banking industry was one of the first industries to leverage and promote the self-service technology concept to allow the client to become a virtual teller for banks, carrying out transaction for their account in much the same way a personnel would. Self-service distribution channels can be used as a competitive differentiator and have an implication for banks to design more innovative service. Customer participation has always been an indispensable part of any service delivery process. Even in an automatic service customer participation is essential for considerable service performance of ATMs. However, in spite of the increasing number of banks, building new ATMs, there is little academic research on this topic and the implications of this relationship between customer participation and ATMs service performance. Hypotheses formed the basis for this research and were empirically tested by means of regression model. The empirical results (n=1500) identified, that there is a positive impact of customer participation on ATMs service performance. Results of the study show that service performance of ATMs has significant difference across the types of the banks. It means that private banks’ customers recorded higher level of service performance from their ATMs, and the level of participation made by the customer is high at private banks. Participation needed for ATMs service performance was identified as essential at all ATMs. The research concluded that customer participation needed has an effect on ATMs service performance. It is very important to educate the customer for participation in ATMs service delivery. Therefore it is necessary for researchers to design effective system to enhance customer participation in the delivery of banking services via ATMs.
Keywords: Customer Participation; Service Performance; ATM; Banking Industry